Application of Fourier Transform Infrared Spectrophotometry Method for Analysis of Metformin Hydrochloride in Marketed Tablet Dosage Form - Nerdy Nerdy; Linda Margata; Dian Ika Perbina Meliala; Bunga Mari Sembiring; Selamat Ginting; Effendy De Lux Putra; Atika Mulyati; Tedy Kurniawan Bakri (Jurnal Kimia Valensi, 2021)
The first line drug given for monotherapy for diabetes mellitus type 2 is metformin hydrochloride, which is a biguanide antihyperglycemic drug. The aim of this research was to develop, validate, and apply the Fourier Transform Infrared spectrophotometry method to identify and determine metformin hydrochloride in marketed tablet dosage form. This research included preparation of standard, analysis of samples, and validation of method. The specific wavenumber obtained for qualitative analysis was 1645.68 cm–1 and 1574.8 cm–1. The specific area obtained for quantitative analysis with a single baseline ranged from 1701.53 cm–1 to 1535.66 cm–1. All metformin hydrochloride marketed tablet dosage forms were analyzed and met all of the qualitative and quantitative requirements. The methods met the requirements of method validation for accuracy with a percentage of recovery of 100.22 %, precision with relative standard deviation of 0.48 %, linearity with a correlation coefficient of 0.9992, limit of detection of 11.17 mg per mL, limit of quantitation of 33.84 mg per mL, and good specificity results. In this study, the Fourier Transform Infrared spectrophotometry method was successfully developed and validated for application in identification and determination of metformin hydrochloride in marketed tablet dosage form.